The Double Challenge of Market and Social Incorporation: Progress and Bottlenecks in Latin America - Martínez Franzoni, Juliana (2014)
Has the past decade of sustained economic growth and political transformations reversed Latin America's historical failure to secure market and social incorporation? To address this question this article draws on the experiences of Bolivia, Brazil, Chile, Peru and Uruguay by distinguishing between short‐term outcomes – which may depend on benign international conditions – and policy changes, which are more important for long‐term performance. It highlights the overall success of both Brazil and Uruguay and shows that the other countries have made more progress in terms of social than market incorporation.